Tontines of today and tontines of tomorrow? Lessons from west african tontines - (:unkn) unknown (My University, 2025)
Tontine is an informal saving and credit practice. In Africa, the tontinier phenomenon is important. The emergency context of the tontines is closely linked to the difficulties of access to credit for a part of the population. The importance of the informal sector in the economy implies the development of these organisations which rely on an association of individuals who will have to cooperate to achieve their personal goals in a specific organisational framework, here, relatively limited and united. This specificity is due to the governance mechanisms applied (traditionally, a necessary trust between the members of the tontine); to the purpose of these organizations (generally, the constitution of a savings - a fund -). An underlying question is the evolution of the organization of tontine and, more generally, of the tontine model of tomorrow. In this paper, we study tontines located in Mali and Ivory Coast (West Africa).
Keywords: African Research